Holistic Admissions in Nursing: We Can Do This - GLAZER, GREER (J Prof Nurs, 2016)
Research shows that holistic admissions review practices can increase diversity across students without decreasing the workforce preparedness and academic success of students. Therefore, many disciplines have readily adopted the widespread use of holistic admissions review. Despite its proven effectiveness in addressing student diversity, nursing has been slow to implement holistic admissions review. The purpose of this study was to gain a better understanding of the barriers to implementing holistic admissions review in nursing and the feasibility of adopting holistic admissions review across nursing programs. A biphasic qualitative research study was conducted with nursing deans from across the United States. Qualitative data collection consisted of two phases of focus group discussions conducted over a 3-month period. The qualitative data were analyzed using content analysis. The categories and subcategories identified in Phase 1 informed the discussion in Phase 2. One overarching category from Phase 1 was identified, which was the lack of nursing schools’ knowledge regarding holistic admissions review. Four subcategories also identified in Phase 1 included the need for better dissemination of evidence, the need for additional support from university leaders and administrators, the need for legal guidance to facilitate implementation of holistic admissions review, and ensuring appropriate resources to support the holistic admissions review process. Three categories emerged in Phase 2, which included everyone’s buy-in is required, the need for a model, and a need for training. The adoption of holistic admissions review in nursing may be feasible. However, certain barriers need to be overcome so that nursing schools can successfully take on this process. Therefore, five recommendations have been developed to assist nursing schools in the implementation of holistic admissions review. These recommendations include increasing knowledge and understanding of holistic admissions review among nursing deans; obtaining buy-in and support for holistic admissions review and conducting a self-assessment of current admissions practices; providing nursing administrators, faculty, and staff with diversity training; and conducting further research to identify factors most critical for success in nursing. Although the transition to a holistic admissions process requires some effort, arming ourselves with the appropriate tools will mitigate barriers during implementation.